Development of the Extrusion Based Food 3D Printer Machine by Modifying Fused Deposition Modelling (FDM) 3D Printer - Dewi, Tiara Kusuma; Bestiara, Fini; Saptaji, Kushendarsyah; Ramadhan, Anwar Ilmar; Triawan, Farid; Azhari, Azmir (Applied mechanics and materials, 2024)
The additive manufacturing (AM) technique is the method to objectify a design by adding the material layer-by-layer. AM for food 3D printing application is used to modify the process of food production in aspects of shape, color, flavor, texture, and nutrition. However, the price of food 3D printers available in the market is too high compared to the benefits they can provide. Addressing this issue, modifying the traditional fused deposition modelling (FDM) 3D printer can be a cheaper alternative that offers more advantages for food production process. This study provides the modification of the FDM 3D printer, such as the designing, fabricating, and setting the new extrusion mechanism to develop the food 3D printer. The modifications are mainly in the extrusion mechanism where the printing material changes from filament into semi-fluid food material. The proposed food 3D printer then tested by printing two different using semi-fluid food materials, i.e., strawberry, and peanut jam. In addition, two different shapes, three different dimensions, and two travel speeds are being selected for the printing test, i.e., 40 and 60 mm/s. As a result, the FDM 3D printer was modified and converted successfully into a food 3D printer. Based on the printing outcomes, it was showed that the strawberry jam has a better surface finish than peanut jam due to its texture consistency. Moreover, the strawberry material also has a lower percentage of error particularly when printed at slower speed. This research is expected to contribute to the development of affordable food 3D printers in Indonesia.